2014
DOI: 10.3748/wjg.v20.i43.16323
|View full text |Cite
|
Sign up to set email alerts
|

Lubiprostonevs Sennain postoperative orthopedic surgery patients with opioid-induced constipation: A double-blind, active-comparator trial

Abstract: Both lubiprostone and Senna improved constipation-related symptoms and QOL in opioid-induced constipation, with no significant between-group differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Concerning prucalopride, there is only one published study available showing that both the 2 mg and 4 mg once-daily doses significantly increase spontaneous bowel movements in these patients, but only during the first two weeks of treatment [ 29 ]. Concerning lubiprostone, the available data (two published studies [ 142 , 145 ] and four abstracts [ 38 , 40 , 41 , 44 ]) seem to suggest that the drug may be useful in the treatment of OIC, even though it is possible that this effect is limited to some subtypes of patients. Compared with placebo, lubiprostone was able to improve symptoms related to OIC [ 142 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning prucalopride, there is only one published study available showing that both the 2 mg and 4 mg once-daily doses significantly increase spontaneous bowel movements in these patients, but only during the first two weeks of treatment [ 29 ]. Concerning lubiprostone, the available data (two published studies [ 142 , 145 ] and four abstracts [ 38 , 40 , 41 , 44 ]) seem to suggest that the drug may be useful in the treatment of OIC, even though it is possible that this effect is limited to some subtypes of patients. Compared with placebo, lubiprostone was able to improve symptoms related to OIC [ 142 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with placebo, lubiprostone was able to improve symptoms related to OIC [ 142 ]. Another study showed no advantage over the less expensive senna [ 145 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the occurrence of OIC or the health care utilization and costs associated with OIC in these patients. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Over 18 clinical studies have used the PAC-SYM, since its validation in 1999: 14 of these have been reported since 2010. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Moreover, these trials have examined a range of interventions including sacral nerve stimulation, 20 lifestyle changes 19 and pharmacological agents. 6,11 Historically, a reduction in total score of 1 point or more has been used as the cut-off to define a positive response to treatment, 2 implying that this is a meaningful improvement.…”
Section: Introductionmentioning
confidence: 99%